IMMERSIVE TECHNOLOGIES IN ITALIAN CULTURAL TOURISM: AN EXPLORATORY ANALYSIS OF VISITOR SATISFACTION AND PREDICTIVE MODELING - Assia LIBERATORE; Ana Elisa SOUSA; Paula CARDOSO; Sónia PAIS (Studia Universitatis Babeş-Bolyai Negotia, 2025)
This study explores the impact of Augmented Reality (AR) and Virtual Reality (VR) on cultural tourism in Italy. The methodology is twofold. By analyzing visitor satisfaction through a comprehensive survey conducted across 18 museums in northern, central and southern Italy, we aim to understand the role of these technologies in enhancing the tourism experience. An agent-based simulation using NetLogo was employed to predict visitor satisfaction based on various demographic and experiential factors, utilizing monthly seasonal data from the Italian National Institute of Statistics (ISTAT).